CORRELATION OF FEMALE SEXUAL DYSFUNCTION WITH OCCUPATIONAL BURNOUT IN MARRIED NURSE - Ali, Zulfikar; Aulia, Kindy; Rahardjo, Harrina Erlianti (Indonesian Journal of Urology, 2025)
Objective: This study aims to see the correlation between occupational burnout and sexual dysfunction in Indonesian female nurses. Material & Methods: A cross sectional study was conducted in Kardinah General Hospital, Tegal, Central Java, Indonesia between January 2022, and March 2022. An anonymous, self-administered online questionnaire was used. Our study subjects are female nurses from outpatient clinics, inpatient wards, high/intensive care unit, emergency unit, and operating theater. We distributed online questionnaires to female nurses who matched our inclusion and exclusion criteria. Occupational burnouts among nurses were assessed using Copenhagen Burnout Inventory (CBI), while Female sexual dysfunction (FSD) was assessed using Female Sexual Function Index (FSFI). Statistical analysis was conducted using IBM SPSS software ver 25.0. Results: A total of 285 nurses participated as samples of this study, 164 nurses (57.54%) were in the low workload group and 121 nurses (42.46%) in the high workload group. The prevalence of sexual dysfunction in female nurses in this study was as high as 87.7% While occupational burnout in high and low workload nurses in our study was 42.2% and 19.5%, respectively. The analysis shows a significant negative correlation between CBI score, sub scores, and burnout status to FSFI score (p < 0.05) although these correlations were weak. Our data proved that there were no independent variables that can become a predictor variable. Conclusion: Married female nurses have a relatively high occupational burnout and are prone to sexual dysfunction. This study showed statistically significant but weak correlation between occupational burnout with sexual dysfunction in married female nurses from the CBI total score, subscores and burnout status with FSFI total score and subscores in terms of lubrication, orgasm, satisfaction, and pain. Keyword: Female sexual dysfunction, occupational burnout, married, nurse, CBI, FSFI.